2010
DOI: 10.1128/jb.00741-09
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Functional Analysis of the Neisseria gonorrhoeae Fur Regulon

Abstract: To ensure survival in the host, bacteria have evolved strategies to acquire the essential element iron. In Neisseria gonorrhoeae, the ferric uptake regulator Fur regulates metabolism through transcriptional control of iron-responsive genes by binding conserved Fur box (FB) sequences in promoters during iron-replete growth. Our previous studies showed that Fur also controls the transcription of secondary regulators that may, in turn, control pathways important to pathogenesis, indicating an indirect role for Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
99
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(108 citation statements)
references
References 57 publications
8
99
1
Order By: Relevance
“…This gonococcal fur mutant strain does not exhibit a growth deficiency compared to the wild-type strain (Daou et al, submitted). To initially identify genes which were activated by Fur, we first screened N. gonorrhoeae F62 fur mutant and wild-type strains for the expression of a subset of genes which were previously reported in N. gonorrhoeae strain FA1090 to be activated in the presence of iron and to contain a predicted Fur box in the promoter region (21,38). Initial screening was performed in cultures grown under iron-replete and -depleted conditions using semiquantitative RT-PCR (data not shown).…”
Section: Identification Of Fur-activated Genes In N Gonorrhoeae F62mentioning
confidence: 99%
See 3 more Smart Citations
“…This gonococcal fur mutant strain does not exhibit a growth deficiency compared to the wild-type strain (Daou et al, submitted). To initially identify genes which were activated by Fur, we first screened N. gonorrhoeae F62 fur mutant and wild-type strains for the expression of a subset of genes which were previously reported in N. gonorrhoeae strain FA1090 to be activated in the presence of iron and to contain a predicted Fur box in the promoter region (21,38). Initial screening was performed in cultures grown under iron-replete and -depleted conditions using semiquantitative RT-PCR (data not shown).…”
Section: Identification Of Fur-activated Genes In N Gonorrhoeae F62mentioning
confidence: 99%
“…Microarray analysis of N. gonorrhoeae FA1090 grown under iron-replete and -depleted conditions reported that 300 genes were repressed by growth under iron-replete conditions while 107 genes were induced (21,38). For those genes regulated by iron, putative Fur boxes were predicted based on the consensus Fur binding sequences from N. gonorrhoeae, P. aeruginosa, and E. coli (21,38). Using this analysis 92 gonococcal genes were shown to contain predicted Fur boxes, and of these 28 were shown to bind Fur in a Fur titration assay (FURTA), including 10 ironactivated genes (38).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The binding of Fe(II) induces a conformational change that allows Fur to behave as a transcriptional repressor by blocking access of RNA polymerase to the DNA. This mechanism of Fur regulation has been identified across a diverse range of bacteria, including the model organism Escherichia coli and the human pathogens Helicobacter pylori and Neisseria gonorrhoeae as well as the Gram-positive bacterium Bacillus subtilis (7)(8)(9)(10). Although Fur was originally considered a regulator of genes involved in iron uptake, it is becoming more apparent that it functions as a global regulator involved in a variety of processes such as virulence, motility, and response to oxidative stress (11,12).…”
mentioning
confidence: 99%